Effect of Type and Concentration Strong Acid Variety on Viability, Vigor and Growth of Arabica Coffee Seeds Sigararutang Variety on Different Planting Media - Ai Komariah; Elly Roosma Ria; Nunung Sondari (Ann Publisher, 2026)
Background. The dormancy of Arabica coffee seeds is one of the main obstacles in the provision of quality seeds because the hard seed skin causes the germination process to take place slowly and is not uniform. Purpose. This study aims to obtain the best combination of types and concentrations of strong acids and planting media in increasing the viability, vigor, and growth of Arabica coffee seeds of the Sigararutang variety. Method. The research was carried out at the Greenhouse of the Faculty of Agriculture, Winaya Mukti University, using a Split-Plot Design with three replications. The main plot consists of two planting media, namely a mixture of soil: husk charcoal (2:1) and soil: manure (2:1), while the subplot is a combination of three types of strong acids (H₂SO₄, HNO₃, and HCl) at concentrations of 0%, 5%, 10%, 15%, and 20%. The parameters observed included germination age, germination power, growth rate, percentage of Soldier phase, percentage of Kepel phase, and seedlings height aged 91 days after planting. The data was analyzed using analysis of variance (ANOVA) and continued with the Duncan’s Multiple Range Test (DMRT) at a real level of 5%. Results. The results showed that there was a real interaction between the combination of strong acids and planting media on germination age and germination power. Treatment of HNO₃ 5% and HCl 10% on soil media: husk charcoal produces the fastest germination rate, while HNO₃ 5%, H₂SO₄ 20%, and HCl 10% on the same media result in the highest germination rate of 100%. The 5% HNO₃ treatment provides the best growth speed and seedlings height up to 8.11 cm at the age of 91 days after planting. Conclusion. Soil media: husk charcoal consistently yields better results than soil media: manure on most growth parameters. Thus, scarification using HNO₃ 5% combined with soil media: husk charcoal is recommended as the most effective pre-planting treatment to accelerate germination, increase viability and vigor, and produce more optimal early growth of Arabica coffee seeds.